Diffuse Effect of the Tungsten Doped Ba(Zr0.10Ti0.90)O3 Ferroelectric Ceramics - Moura, Francisco; Simões, Alexandre Zirpoli; Gimenes, R.; Perazolli, Leinig [UNESP]; Zaghete, Maria Aparecida [UNESP]; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (My University, 2009)
Barium zirconate titanate Ba(Ti0.90Zr0.10)O3 ceramics doped with WO3 (BZT:2W) have been prepared by a traditional solid phase reaction. The effect of temperature on the structural and electrical properties was investigated. X ray diffraction data evidenced formation of secondary phases for the samples sintered at 1300oC end 1350oC while the pure phase was attained at 1200oC. A modified Curie-Weiss law was used to describe the diffuseness of a phase transition. As temperature increases, the maximum dielectric permittivity decreased. The fine-grained sample showed a 'diffuse-like' ferroelectric behavior. The dielectric permittivity reaches a maximum value (εm ~6420 at 10 kHz) for the ceramics sintered at 1200oC for 4 hours.
Keywords: Barium zirconate titanates; Dielectric permittivities; Effect of temperature; Ferroelectric behavior; Solid phase reaction; Structural and electrical properties; Temperature increase; X-ray diffraction data; Barium zirconate; Electric properties; Exhibitions; Ferroelectric ceramics; Permittivity; Sintering; X ray diffraction; Zirconium; Ceramic materials